Indirect Quantification of Glyphosate by SERS Using an Incubation Process With Hemin as the Reporter Molecule: A Contribution to Signal Amplification Mechanism - López-Castaños, Karen A.; Ortiz-Frade, Luis A.; Méndez, Erika; Quiroga-González, Enrique; González-Fuentes, Miguel A.; Méndez-Albores, Alia (Frontiers in Chemistry, 2020)
The indirect determination of the most used herbicide around the world, glyphosate, was achieved by the SERS technique using hemin chloride as the reporter molecule. An incubation process between hemin and glyphosate solutions was required to obtain reproducible Raman signal on SERS substrates consisting of silicon decorated with Ag nanoparticles (Si-AgNPs). At 780 nm of excitation wavelength, SERS spectra from hemin solutions do not show extra bands in the presence of glyphosate. However, the hemin bands increase in intensity as a function of glyphosate concentration, allowing the quantification of the herbicide using as marker band the signal associated to the ring breathing mode of pyridine at 745 cm-1. The linear range was from 1x10^-10 to 1x10^-5 M and the limit of detection (LOD) was 9.59x10^-12 M. This methodology was successfully applied to the quantification of the herbicide in honey. From Raman experiments with and without silver nanoparticles it was possible to state that the hemin is the species responsible of absorption in absence or presence of the herbicide, via vinyl groups. Likewise, when the glyphosate concentration increases, a subtle increase occurs in the planar orientation of the vinyl group at position 2 in the porphyrin ring of hemin over silver surface, favoring the reduction of the molecule. The total Raman signal of the hemin-ghyphosate incubated solutions includes a maximized electromagnetic contribution by the use of the appropriate laser excitation, and chemical contributions related to charge transfer between silver and hemin, and from resonance properties of Raman scattering of hemin. The incubation of the reporter molecule with the analyte before conjugation with the SERS substrate has not been explored before and could be extrapolated to other reporter-analyte systems that depend on a binding equilibrium process.